Differences in itch and pain behaviors accompanying the irritant and allergic contact dermatitis produced by a contact allergen in mice. (September 2019) - Zhang, Zhe; Malewicz, Nathalie M.; Xu, Xiaoyun; Pan, Jianhao; Kumowski, Nina; Zhu, Tao; Shimada, Steven G.; Nie, Hong; LaMotte, Robert H.
Abstract: Introduction: Irritant contact dermatitis (ICD) and allergic contact dermatitis (ACD) are inflammatory skin diseases accompanied by itch and pain. Irritant contact dermatitis is caused by chemical irritants eliciting an innate immune response, whereas ACD is induced by haptens additionally activating an adaptive immune response: After initial exposure (sensitization) to the hapten, a subsequent challenge can lead to a delayed-type hypersensitivity reaction. But, the sensory and inflammatory effects of sensitization (ICD) vs challenge of ACD are insufficiently studied. Therefore, we compared itch- and pain-like behaviors and inflammatory reactions evoked in mice during the sensitization (ICD) vs challenge phase (ACD) of application of the hapten, squaric acid dibutylester (SADBE). Objectives: Our aim was to compare itch- and pain-like behaviors and inflammatory reactions evoked in mice during the sensitization (ICD) vs challenge phase (ACD) of application of the hapten, squaric acid dibutylester (SADBE). Methods: Mice were sensitized on the abdomen with 1% SADBE (ACD) or vehicle treated (ICD, control). Spontaneous and stimulus-evoked itch- and pain-like behaviors were recorded in mice before and after 3 daily challenges of the cheek with 1% SADBE (ACD, ICD). Cutaneous inflammation was evaluated with clinical scoring, ultrasound imaging, skin thickness, histology, and analyses of selected biomarkers for contact dermatitis, IL-1β, TNF-α, CXCL10, and CXCR3. Results: Allergic contact dermatitis vs ICD mice exhibited more spontaneous site-directed scratching (itch) and wiping (pain). Allergic contact dermatitis—but not ICD—mice exhibited allodynia and hyperalgesia to mechanical and heat stimuli. Inflammatory mediators IL-1β and TNF-α were upregulated in both groups as well as the chemokine receptor, CXCR3. CXCL10, a CXCR3 ligand, was upregulated only for ACD. Inflammatory responses were more pronounced in ACD than ICD. Conclusion: These findings provide new information for differentiating the behavioral and inflammatory reactions to hapten-induced ICD and ACD. Abstract : Supplemental Digital Content is Available in the Text.